Hydrostructure of Groundwater Manifestation of Gedongsongo Geothermal Ungaran, Semarang, Central Java, Indonesia - Hisan, Nazwa Khoiratun; Jasaputra, Ludovikus Damardika; Bernaldo, Pius Artdanno; Karlina, Nur Alif Yusuf Putra; Arhananta, Arhananta (Lembaga Penelititan dan Pengabdian kepada Masyarakat - Institut Teknologi Adhi Tama Suraba, 2020)
Groundwater is an important element of the hydrological cycle in geothermal systems. The geological structure of the Plio-Pleistocene volcano and different lithological variations affect the type and response of groundwater to rocks. The research area is located around the Gedongsongo Temple complex, Mount Ungaran, Central Java. Based on the field check location, there are three variations of lithology, the first lithology is a breccia with andesite, basalt, and pyroclastic fragments. The NW-SE-oriented geological structure is flattened to the right slip fault which is the fracture aquifer system on the Southern Slope of Mount Ungaran. In the research area, there is an anomaly in the form of deflection of flow direction pattern caused by structural control factor in the form of fracture, the fracture which becomes the fluid channel media is a tension joint on the shear zone with Northwest strike with dip direction toward Northeast which has NW-SE orientation of right slip fault.